TEGANGAN SEKUNDER PADA STRUKTUR RANGKA BATANG - Purba, Parhimpunan (Diponegoro University, 2007)
In our previous analysis of trusses, it was always assumed that the truss members are joined by ideal hingesand that loads are applied only at joints. The centroidal axes all of members are stright, coincide with thelines connecting the joint center, and lie in a plane that also contains the lines of action of all the loads andreaction. Thus the members of truss are subjected to axial force only, and these can be determined by staticmethod. A stress analysis base on these assumtion leads to the determination of so â€“ called â€œprimarystressesâ€.In actual cases the joint are usually riveted or welded; and because of this fact the members undergo, notonly axial forces, but also bending stresses from secondary moment, cuased by this condition are calledâ€œsecondary stressesâ€. In discusing secondary stresses we shall consider only trussses in one plane andassume that this plane represents the plane of symmetri for all members and that external loads are acting inthe same plane. Of these the most important are caused by the fact that the joint are rigid, and hence themembers are not free to change their relative directions when the truss is deformed. This problem canlikewise be solved very eficiently by means of moment distibution.From the first analyze result, it was obtained the scondary tension ratio with the primary tension at the pullshaft about 19.20 %. This result is significant that it will increase the existence of primary tension. At theanalyze by SAP 2000 is obtained that the end tension much more lower than the scondary tension in the firstanalyze. This is need to obtain attention at planning trusses.